STRATEGY OF HUMAN RESOURCES AND MODERN MARKETING ABILITY TOWARDS IMPROVING THE CREATIVE ECONOMY THROUGH SUPPORT GOVERNMENT IN LAKE TOBA TOURIST DESTINATION - Bunga Aditi (CV. RADJA PUBLIKA, 2025)
In improving tourist destinations, especially concerning the process that will be developed by creative business actors to be able to improve the creative economy, modern human resource and marketing capabilities are needed which illustrate the existence of strategies carried out through internal processes so that the impact has an influence in improving the creative economy of the Lake Toba tourist destination. The purpose of this studyreview and analyze HR Capabilities and Online Marketing Strategies for Government Support in improving the creative economy at Lake Toba tourist destinations.This study uses data analysis methods using softwareAndSmartPLS.The results of the study showedModern HR and marketing capabilities have a significant effect on government support. Government support has a significant effect on increasing the creative economy. Government support as an intervening variable has a significant impact on increasing the influence of Modern HR and Marketing capabilities on increasing the creative economy.